2016
DOI: 10.2485/jhtb.25.357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotinamide on Cytotoxicity-induced Morphological Changes in Osteoblastic Cells <i>In Vitro</i>

Abstract: Excessive chemical and dynamic stimulation to a cell increases oxidative stress in the cell and causes cellular dysfunction. Osteoblast counts decrease under oxidative stress, and it is known that in the healing process after surgical treatment, bone regeneration treatment, bone fracture, and dental implant treatment, apoptosis is induced, and there is a decrease in bone tissue. In addition, hydrogen peroxide induces cell death via oxidative stress, and vitamin B is known to be involved as a coenzyme of the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Due to the appreciable stability with time of the complex in DMSO under physiological-like conditions, the complex could be evaluated as potential cytotoxic agent. Previously, many studies were reported the cytotoxicity properties of NA [67][68][69][70]. Hence, the cytotoxicity of the BBHMP and its platinum(II) complex was examined for human prostate (DU145) and breast (MCF7) cancer cell lines with an MTT assay.…”
Section: Cytotoxicity Resultsmentioning
confidence: 99%
“…Due to the appreciable stability with time of the complex in DMSO under physiological-like conditions, the complex could be evaluated as potential cytotoxic agent. Previously, many studies were reported the cytotoxicity properties of NA [67][68][69][70]. Hence, the cytotoxicity of the BBHMP and its platinum(II) complex was examined for human prostate (DU145) and breast (MCF7) cancer cell lines with an MTT assay.…”
Section: Cytotoxicity Resultsmentioning
confidence: 99%
“…On the other hand, one of the most common problems in tissue engineering is that excessive cell stimulation can cause cytotoxicity due to the generation of reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ), and consequently, lead to cell dysfunction and apoptosis. Thus, Ito et al examined the effects of nicotinamide (NAM) in a cytotoxic-induced situation in rat bone marrow cells [22]. They used a H 2 O 2 solution as the cytotoxic reagent and compared cells with and without a pre-treatment of NAM.…”
Section: Discussion: B-vitamins As a Tool In Tissue Engineeringmentioning
confidence: 99%